ANALISIS PENGARUH RASIO PROFITABILITAS TERHADAP HARGA SAHAM PADA PERUSAHAAN SUBSEKTOR SEMEN YANG TERDAFTAR DI BEI - KAMILAH I, INSI Kamilah (Jurnal Akuntansi AKUNESA, 2012)
This research aims to determine the effect of the ratio profitability on the company's stock price of cement which listed on Indonesian Stock Exchange. Ratio profitability is calculated using the instrument of ROA, ROE, EPS, and NPM as variable Method used in this research is descriptive. Multiple linier regression analysis is used for analytical method. The conclude of the research is ratio profitability simultaneously significant affect on the company's stock price of cement which listed on Indonesian Stock Exchange. Keywords: Ratio profitability. Stock price. ROA, ROE, EPS, NPM.